2021
DOI: 10.3390/ijms222111811
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Antibacterial Activity of Selected Metal Nanoparticles and Alterations within the Antioxidant Defence System in Escherichia coli, Bacillus cereus and Staphylococcus epidermidis

Abstract: The antimicrobial activity of nanoparticles (NPs) is a desirable feature of various products but can become problematic when NPs are released into different ecosystems, potentially endangering living microorganisms. Although there is an abundance of advanced studies on the toxicity and biological activity of NPs on microorganisms, the information regarding their detailed interactions with microbial cells and the induction of oxidative stress remains incomplete. Therefore, this work aimed to develop accurate ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
(147 reference statements)
1
6
0
Order By: Relevance
“…Considering this, the increase in CAT activity in E. coli cells treated with NPs may result from stimulated HPI activity dependent on the presence of H 2 O 2 . This is in agreement with our previous findings, which revealed that the tested NPs, especially ZnO-NPs and Cu-NPs, induced the formation of H 2 O 2 along with other types of ROS in bacterial cells [40]. Additionally, a positive correlation between CAT and PER activity along with the expression of katG and katE genes was confirmed by statistical analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering this, the increase in CAT activity in E. coli cells treated with NPs may result from stimulated HPI activity dependent on the presence of H 2 O 2 . This is in agreement with our previous findings, which revealed that the tested NPs, especially ZnO-NPs and Cu-NPs, induced the formation of H 2 O 2 along with other types of ROS in bacterial cells [40]. Additionally, a positive correlation between CAT and PER activity along with the expression of katG and katE genes was confirmed by statistical analysis.…”
Section: Discussionsupporting
confidence: 93%
“…•− [40]. Similarly, the increased relative expression level of katE in B. cereus under Cu-NPs exposure was associated with a stimulation of CAT activity.…”
Section: Discussionmentioning
confidence: 88%
“…Overall, Metryka and colleagues demonstrate that most of these NPs induce a strong production of all ROS (i.e., H 2 O 2 , •OH, 1 O 2 , O 2 • − ) mainly in S. epidermidis; while this increase is more contrasted in B. cereus and E. coli. Conversely, CuNPs seem to be the particles most likely to stimulate the production of ROS, regardless of the bacteria tested [87].…”
Section: Results Of the Literature Searchmentioning
confidence: 86%
“…The mechanism of the inhibitory effect of metal NPs on enzymes seems to be due to their interaction with sulfhydryl groups (Manceau et al, 2008;Metryka et al, 2021;Slavin et al, 2017). The degree of ecotoxicity of NPs depends not only on the dose but also on the class of the enzyme.…”
Section: Discussionmentioning
confidence: 99%